Corporate dieting: Persuasive use of metaphors in downsizing - Heiko Hoßfeld (Management Revue, 2013)
This paper considers how companies use their own mass communication media to create, with the aid of metaphors, a legitimizing image of their practices. The analysis is based on the example of two banks, both of which undertook massive staff and cost reductions between 2001 and 2003. Downsizing measures like theirs are often met with resistance if they conflict with the interests, values or worldviews of stakeholders. Companies approach this threat of resistance by building a linguistic façade of legitimacy that suggests conformity with prevailing ideas of good or correct managerial conduct. Our metaphor analysis, which covers all publicly accessible texts of the two banks' own mass communication, identifies nine metaphoric concepts, which we further condense into three persuasive meta concepts: concealing metaphor, euphemistic metaphor, and urgency and control metaphor each fulfil different persuasive functions and vary systematically according to the conditions surrounding the managerial practice.
Keywords: D83; G21; J63; 650; metaphors; rhetoric; symbolic management; legitimacy; downsizing; layoffs; banks; Öffentlichkeitsarbeit; Rhetorik; Personalabbau; Bank; Deutschland